1991
DOI: 10.1302/0301-620x.73b4.2071654
|View full text |Cite
|
Sign up to set email alerts
|

Axial movement and tibial fractures. A controlled randomised trial of treatment

Abstract: Diaphyseal fractures of the tibia in 80 patients were treated by external skeletal fixation using a unilateral frame, either in a fixed mode or in a mode which allowed the application of a small amount of predominantly axial micromovement. Patients were allocated to each regime by random selection. Fracture healing was assessed clinically, radiologically and by measurement of the mechanical stiffness of the fracture. Both clinical and mechanical healing were enhanced in the group subjected to micromovement, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(120 citation statements)
references
References 19 publications
1
117
0
2
Order By: Relevance
“…The main aim of such studies is to determine when the external fixation device can be removed without risk of a refracture or angulation and when an increased loading of the fracture can be recommended to the patient. Most of the studies [8,21,25,32,43] provided a good and objective database to inform this decision. Decisions about reoperations or additional operations, which might be necessary, could be supported by the data achieved from these measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main aim of such studies is to determine when the external fixation device can be removed without risk of a refracture or angulation and when an increased loading of the fracture can be recommended to the patient. Most of the studies [8,21,25,32,43] provided a good and objective database to inform this decision. Decisions about reoperations or additional operations, which might be necessary, could be supported by the data achieved from these measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are only a few studies [4,8,21,23,25,32,41] which monitored the stiffness of healing fractures in a sufficiently large number of patients to be able to draw conclusions from the results. The largest study of direct measurement of bone stiffness was presented by Richardson et al [32] on 212 patients with tibial fractures treated by external fixation.…”
Section: Clinical Studies Using Bone Stiffness Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of the genetic mechanism regulating fetal skeletogenesis also play a role in adult skeletal regeneration (Vortkamp et al, 1998;Ferguson et al, 1999), the mechanical environment is known to play a key role in regulating the outcomes of fracture repair (Goodship and Kenwright 1985;Kenwright and Goodship 1989;Kenwright et al, 1991;Chao et al, 1998;Goodship et al, 1998;Goodship et al, 2009). A number of hypotheses have been proposed for how MSC differentiation is regulated by the mechanical environment during events such as fracture repair.…”
Section: Repairmentioning
confidence: 99%
“…Many authors have demonstrated that although compression is necessary during the early stages of fracture healing 5,8,11 loading must be cyclic at a later stage, a principle applied not only to fractures but also to non-unions, as demonstrated by Ilizarov. 4 External fixation not only responds to the first requirements but it is the only aid which allows a mechanical modulation of the healing process.…”
Section: Introductionmentioning
confidence: 99%